How Osteoporosis Looks Like in CT Scan Images: An Alternative Osteoporosis Assessment - Genisa, Maya; Abdullah, Johari Yap; MD Yusoff, Bazli Bin; Aryenti, Aryenti; Juniarti, Juniarti (Journal of Health and Nutrition Research, 2025)
Osteoporosis is a silent degenerative disease that commonly affects the elderly, leading to decreased bone density and increased risk of fractures. Dual-Energy X-ray Absorptiometry (DEXA) is the standard tool for assessing Bone Mineral Density (BMD), but its limited availability and high cost in many healthcare facilities, especially in developing countries like Indonesia, necessitate alternative diagnostic methods. This study aims to assess the potential use of Computed Tomography (CT) scan images as a substitute for DEXA in detecting osteoporosis. The objective is to analyze bone texture attributes from CT images to differentiate between normal and osteoporotic bone structures. The method involved collecting CT scan data from patients at Hospital Universiti Sains Malaysia (HUSM). The vertebrae regions were segmented from the abdominal CT images using image processing techniques to isolate bone tissue. Four image-derived texture attributes—Roughness, Contrast, Greyscale, and Phase—were then extracted using MATLAB-based analysis. The results showed that osteoporotic bones had higher values in Roughness and Contrast, and lower values in Greyscale and Phase compared to normal bones. Among these, Roughness was identified as the most sensitive attribute in detecting changes associated with osteoporosis. These findings indicate that CT scan images, when analyzed through proper segmentation and texture evaluation, have the potential to serve as a viable alternative for osteoporosis screening, particularly in settings where DEXA is unavailable.